Manajemen Talenta di Era Digital : Sebuah Kajian Literatur - Putri Oktaviani; Zahra Bela Eka Putriana; Niken Bela Enggarani; Netty Merdiaty (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Talent management in the digital era is a complex phenomenon that requires a comprehensive approach in dealing with contemporary organizational transformation. This study aims to explore the dynamics of talent management through a systematic literature review of ten reputable scientific journals covering various organizational and industrial contexts. The research method uses the Systematic Literature Review (SLR) approach with content analysis and narrative synthesis techniques. The findings of the study reveal that talent management is no longer just an administrative function but a strategic strategy that determines the sustainability and competitiveness of organizations in the digital era. The results of the study identify four main dimensions in talent management in the digital era, namely: transformation of management approaches, technology adaptation, development of individual competencies, and the formation of a responsive organizational ecosystem. This research makes a theoretical contribution to produce a comprehensive conceptual framework of cutting-edge talent management practices. The practical implications show the need for a multidimensional approach that pays attention to the technological, psychological, and organizational aspects of managing human resources. This research offers a holistic perspective in understanding the complexity of talent management in the sustainable digital era.